The next step is to solve the recurrence, but let's back up a bit. You should have found that the ODE in terms of the power series expansion for
![y](https://tex.z-dn.net/?f=y)
![\displaystyle\sum_{n\ge2}\bigg((n-3)(n-2)a_n+(n+3)(n+2)a_{n+3}\bigg)x^{n+1}+2a_2+(6a_0-6a_3)x+(6a_1-12a_4)x^2=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge2%7D%5Cbigg%28%28n-3%29%28n-2%29a_n%2B%28n%2B3%29%28n%2B2%29a_%7Bn%2B3%7D%5Cbigg%29x%5E%7Bn%2B1%7D%2B2a_2%2B%286a_0-6a_3%29x%2B%286a_1-12a_4%29x%5E2%3D0)
which indeed gives the recurrence you found,
![a_{n+3}=-\dfrac{n-3}{n+3}a_n](https://tex.z-dn.net/?f=a_%7Bn%2B3%7D%3D-%5Cdfrac%7Bn-3%7D%7Bn%2B3%7Da_n)
but in order to get anywhere with this, you need at least three initial conditions. The constant term tells you that
![a_2=0](https://tex.z-dn.net/?f=a_2%3D0)
, and substituting this into the recurrence, you find that
![a_2=a_5=a_8=\cdots=a_{3k-1}=0](https://tex.z-dn.net/?f=a_2%3Da_5%3Da_8%3D%5Ccdots%3Da_%7B3k-1%7D%3D0)
for all
![k\ge1](https://tex.z-dn.net/?f=k%5Cge1)
.
Next, the linear term tells you that
![6a_0+6a_3=0](https://tex.z-dn.net/?f=6a_0%2B6a_3%3D0)
, or
![a_3=a_0](https://tex.z-dn.net/?f=a_3%3Da_0)
.
Now, if
![a_0](https://tex.z-dn.net/?f=a_0)
is the first term in the sequence, then by the recurrence you have
![a_3=a_0](https://tex.z-dn.net/?f=a_3%3Da_0)
![a_6=-\dfrac{3-3}{3+3}a_3=0](https://tex.z-dn.net/?f=a_6%3D-%5Cdfrac%7B3-3%7D%7B3%2B3%7Da_3%3D0)
![a_9=-\dfrac{6-3}{6+3}a_6=0](https://tex.z-dn.net/?f=a_9%3D-%5Cdfrac%7B6-3%7D%7B6%2B3%7Da_6%3D0)
and so on, such that
![a_{3k}=0](https://tex.z-dn.net/?f=a_%7B3k%7D%3D0)
for all
![k\ge2](https://tex.z-dn.net/?f=k%5Cge2)
.
Finally, the quadratic term gives
![6a_1-12a_4=0](https://tex.z-dn.net/?f=6a_1-12a_4%3D0)
, or
![a_4=\dfrac12a_1](https://tex.z-dn.net/?f=a_4%3D%5Cdfrac12a_1)
. Then by the recurrence,
![a_4=\dfrac12a_1](https://tex.z-dn.net/?f=a_4%3D%5Cdfrac12a_1)
![a_7=-\dfrac{4-3}{4+3}a_4=\dfrac{(-1)^1}2\dfrac17a_1](https://tex.z-dn.net/?f=a_7%3D-%5Cdfrac%7B4-3%7D%7B4%2B3%7Da_4%3D%5Cdfrac%7B%28-1%29%5E1%7D2%5Cdfrac17a_1)
![a_{10}=-\dfrac{7-3}{7+3}a_7=\dfrac{(-1)^2}2\dfrac4{10\times7}a_1](https://tex.z-dn.net/?f=a_%7B10%7D%3D-%5Cdfrac%7B7-3%7D%7B7%2B3%7Da_7%3D%5Cdfrac%7B%28-1%29%5E2%7D2%5Cdfrac4%7B10%5Ctimes7%7Da_1)
![a_{13}=-\dfrac{10-3}{10+3}a_{10}=\dfrac{(-1)^3}2\dfrac{7\times4}{13\times10\times7}a_1](https://tex.z-dn.net/?f=a_%7B13%7D%3D-%5Cdfrac%7B10-3%7D%7B10%2B3%7Da_%7B10%7D%3D%5Cdfrac%7B%28-1%29%5E3%7D2%5Cdfrac%7B7%5Ctimes4%7D%7B13%5Ctimes10%5Ctimes7%7Da_1)
and so on, such that
![a_{3k-2}=\dfrac{a_1}2\displaystyle\prod_{i=1}^{k-2}(-1)^{2i-1}\frac{3i-2}{3i+4}](https://tex.z-dn.net/?f=a_%7B3k-2%7D%3D%5Cdfrac%7Ba_1%7D2%5Cdisplaystyle%5Cprod_%7Bi%3D1%7D%5E%7Bk-2%7D%28-1%29%5E%7B2i-1%7D%5Cfrac%7B3i-2%7D%7B3i%2B4%7D)
for all
![k\ge2](https://tex.z-dn.net/?f=k%5Cge2)
.
Now, the solution was proposed to be
![y=\displaystyle\sum_{n\ge0}a_nx^n](https://tex.z-dn.net/?f=y%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7Da_nx%5En)
so the general solution would be
![y=a_0+a_1x+a_2x^2+a_3x^3+a_4x^4+a_5x^5+a_6x^6+\cdots](https://tex.z-dn.net/?f=y%3Da_0%2Ba_1x%2Ba_2x%5E2%2Ba_3x%5E3%2Ba_4x%5E4%2Ba_5x%5E5%2Ba_6x%5E6%2B%5Ccdots)
![y=a_0(1+x^3)+a_1\left(x+\dfrac12x^4-\dfrac1{14}x^7+\cdots\right)](https://tex.z-dn.net/?f=y%3Da_0%281%2Bx%5E3%29%2Ba_1%5Cleft%28x%2B%5Cdfrac12x%5E4-%5Cdfrac1%7B14%7Dx%5E7%2B%5Ccdots%5Cright%29)